2023
DOI: 10.1109/tts.2023.3257627
|View full text |Cite
|
Sign up to set email alerts
|

Designing AI Using a Human-Centered Approach: Explainability and Accuracy Toward Trustworthiness

Abstract: One of the major criticisms of Artificial Intelligence is its lack of explainability. A claim is made by many critics that without knowing how an AI may derive a result or come to a given conclusion, it is impossible to trust in its outcomes. This problem is especially concerning when AI-based systems and applications fail to perform their tasks successfully. In this Special Issue Editorial, we focus on two main areas, explainable AI (XAI) and accuracy, and how both dimensions are critical to building trustwor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…In addition, AI systems are not always transparent, and it can be challenging to understand their decision-making processes. This lack of transparency makes errors difficult to detect and fix [67]. To address AI unpredictability, researchers have proposed various strategies.…”
Section: When Ai Goes Awry: Understanding the Risks Of Unpredictable ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, AI systems are not always transparent, and it can be challenging to understand their decision-making processes. This lack of transparency makes errors difficult to detect and fix [67]. To address AI unpredictability, researchers have proposed various strategies.…”
Section: When Ai Goes Awry: Understanding the Risks Of Unpredictable ...mentioning
confidence: 99%
“…[66] pointed out that unpredictable errors in AI systems can adversely affect user experience and societal impact. The authors of [67] emphasize the importance of designing AI with a human-centered approach to ensure explainability and accuracy, enhance trustworthiness, and mitigate the risks associated with unpredictable outcomes and unintended biases.…”
Section: Controversy and Implications: The Tessa Chatbot Incident And...mentioning
confidence: 99%
“…Finally, a human-centered approach helps to build trust in the information assessment detection. Users are more likely to trust a system that is transparent, accountable, and open to feedback (Schoenherr et al, 2023). A system that incorporates human expertise can help to provide these qualities, by ensuring that the decision-making process is transparent and that decisions are made based on sound ethical principles.…”
Section: Related Work and Research Gapsmentioning
confidence: 99%
“…For instance, studies conducted at the Massachusetts Institute of Technology (MIT) Media Lab have shown that facial recognition technology is more effective at detecting individuals with lighter skin, especially men, than those with darker skin and women [7]. According to the authors of [8], poorly written algorithms, the use of poisoned, incomplete, or biased training datasets could contribute to the marginalization of certain users.…”
Section: Introductionmentioning
confidence: 99%